Biodegradable Composite of Gelatin Blend Microcrystalline Cellulose for Cd2+, Pb2+, and Cr3+ Adsorption from an Aqueous Solution - Marzia Sultana; Md. Raju Ahmmed; Md Inzamam Ul Hoque; Tanvir Ebna Mohsen; Atol Mondal; Md. Hafezur Rahaman; Moumita Yesmin; Md. Shahedur Rahman; S. M. Nur Alam (Advances in Polymer Technology)
Biodegradable and eco-friendly composite adsorbent was synthesized from modified jute fiber and gelatin and evaluated its efficacy in removing cadmium (Cd2+), lead (Pb2+), and chromium (Cr3+) ions from an aqueous solution. The prepared sample was characterized using Fourier transform infrared spectroscopy, scanning electron microscopy, and energy dispersive X-ray analyses, which revealed that gelatin successfully intercalated into the microcrystalline cellulose matrix. In batch adsorption studies, the effects of pH, adsorbent dosage, initial metal ions concentration, and temperature on the removal of heavy metal ions were investigated. The adsorption capacity of the composite varied with changing parameters, and the maximum removal efficiency obtained for Cd2+, Pb2+, and Cr3+ was 95%, 88%, and 70%, respectively, at pH 6 with 60 ppm of each metal ions concentration and an adsorbent dosage of 1.0 g L−1. Different functional groups in composite adsorbent facilitated heavy metal ions adsorption. Five error analysis methods were used to evaluate the fit the goodness of the data. The equilibrium adsorption and kinetic data were well-fitted with the Langmuir isotherm model and pseudo-second-order, respectively. Moreover, the thermodynamic study showed that the adsorption was spontaneous, chemisorption, and endothermic. Our work offers a sustainable and biodegradable composite synthesized from modified jute fiber and gelatin for multimetal ions removal from an aqueous, which is an eco-friendly alternative to conventional nonbiodegradable adsorbents with potential environmental risks.